INFLUENCE OF STRATEGIC POSITION ANALYSIS ON PERFORMANCE OF MATATU SAVINGS AND CREDIT COOPERATIVES IN KENYA - Mang'ana, Robert Okwoyo; Rotich, Dr. Gladys; Hassan, Dr. Gamaliel; Orwa, Prof. George (European Journal of Business and Strategic Management, 2017)
Purpose: The study aimed at establishing the influence of strategic position analysis on performance of Matatu Savings and Credit Cooperatives in Kenya. Materials and methods: This study adopted a mixed design approach using quantitative cross-sectional survey including causal and descriptive research designs. The target population was 635 registered Matatu Saccos according to (NTSA,2015). Random sampling was adopted as it is advantageous for objectivity. A sample size of 245 was obtained for the study. Primary data was required to gain deeper insight and a better interpretation of the quantitative data. The researcher used a questionnaire for this. In this study, quantitative data was coded and analyzed, while content coding was used in coding the qualitative data. Statistical techniques such as measures of central tendency, dispersion, symmetry and inferential statistics were used to analyze the data. In descriptive analysis, the raw data of the indicators was analyzed and presented in frequency tables and graphs for all the variables depending on the nature of the categorical data of the indicator. Results: The results of the analysis indicated that strategic position analysis has a positive relationship with performance of Matatu Saccos. The strategic position analysis was concluded to have a 0.132 influence on performance of Matatu Saccos. Recommendations: All Matatu Saccos should seek strategic planning process .The National Transport and Safety Authority should make it possible for all Matatu Saccos to be registered and adhere to the regulations. Strategic planning process bring in new and fresh ideas to Matatu Saccos and a being a catalyst for change in an organization which brings growth and success to the organization.